Moderate stability of a scissor double fluorescent triple helix molecular switch for the ultrasensitive biosensing of crop transgene. (12th April 2022) - Chu, Xiuling; Zhu, Desong; Liu, Min; Kong, Lingrang; Ai, Shiyun
Abstract : Schematic of the ultrasensitive biosensing of special genes. (I: traditional molecular beacon detection method; II: scissor DFTHMS; III: three cases of BHQ-1-TFO). Abstract : Bt transgene, a specific crop DNA sequence, has attracted wide attention due to its introduction into crop for insect control. Moreover, this has drawn concern to crop safety. In this study, a scissor double fluorescent triple helix molecular switch (DFTHMS) based on triple helix DNA with alternating T–A○T and C–G○C triads –[–T–A○T/C–G○C/T–A○T/C–G○C–] n – has been shown to be moderately stable, and was successfully used for the ultrasensitive biosensing of Bt transgene. The influencing factors and changing law of the stability of triple helix DNA were also systematically studied. The detection results are quite encouraging. Compared with the reported methods, the nanosensor based on this scissor molecular switch possesses several attractive characteristics: (I) the sensitivity is 10 000 times higher than that of traditional methods by efficient dual fluorescence resonance energy transfer (FRET), (II) it shows generality in the construction of a series of biological sensing systems for special genes due to the convenient design of the scissor switch by changing corresponding recognition sequences (for example, human cancer gene has been detected successfully by this method), (III) it only requires simple operating procedures and mild experimental conditions since no enzymes are involved, which greatly saves time and minimizes the research barriers of interdisciplinary researchers.